Mineral composition of xeric and mesic sheep pasture in Central Hungary - Bajnok, Márta; Halász, András; Török, Gábor; Tasi, Julianna (Animal welfare, Ethology and Housing Systems (AWETH), 2017)
Hungarian sheep farming is based on grasslands. The average grazing period is about 200 days and the winter forage is also calculated with quality hay as well. The pasture based livestock farming is the most beneficial for the animals but there are several veterinary and nutritional problems. Our main objective was to examine two different hydro-ecological types (xeric & mesic) of pasture and compare their micro- and macro nutrients supply. The xeric pasture, located in Kiskunság, with dry, low moisture conditions. This grassland’s nutrient content is under the minimal required level regrading with P, Mg, Cu, Zn, Mn, Na and the rest of the elements are also lack more than 50 %. The mesic pasture with adequate soil moisture, located among Gödöllő-hills, contained sufficient amount of nutrient elements with the exception of Cu and Zn.